(untitled) (Veterinary Science, 2017)
Livestock farms in the northeast of La Pampa were c1assified according to their productivity by using a technical efficiency indexoThis objective was achieved, calculating in the first place , the function of production using a lineal regression model with explanatory variables, such as acres of green onion, acres of pasture, total number of animals and costs of supplementation; then the production frontier was calculated.The technical efficiency index (IET) relates the observed value with the potential valué,according to the fol/owing equation IET =VONF = y/yf. Farms were c1assified into high, medium and low efficiency, according the IET. Linking farms by its size (area) and efficiency, the largest number of the same, are observed (16 above 56) .Final/y, with the explanatory variables by univariate ANOVA, farms were distinguished and concluded that the cost of supplementation was the only explanatory of efficiency variable.